(−)‐ Epigallocatechin‐3‐gallate induces GRP78 accumulation in the ER and shifts mesothelioma constitutive UPR into proapoptotic ER stress. Issue 10 (10th May 2018) - Martinotti, Simona; Ranzato, Elia; Burlando, Bruno
Abstract : GRP78 is a molecular chaperone of the endoplasmic reticulum (ER) that aids proper folding of nascent polypeptides. When unfolded proteins accumulate, GRP78 triggers unfolded protein response (UPR), involving activation of transcription factors like XBP1 and CHOP that may restore cell homeostasis. Increased expression of GRP78 and mild UPR can be constitutive in cancer cells, hindering apoptosis, and promoting cell survival, for example, by GRP78 relocation to the plasma membrane that activates MAPK and PI3 K/AKT pathways. These processes are thought to favor the insurgence of chemoresistance and worsen patient outcome. We have previously shown that (−)‐epigallocatechin‐3‐gallate (EGCG) enhances ROS production and alters Ca 2+ homeostasis in cell lines deriving from therapy‐recalcitrant malignant mesothelioma (MMe). We consider here the EGCG impact on GRP78 and downstream factors by using qRT‐PCR, Western blot, immunofluorescence, caspase assays, GRP78 siRNA silencing, and cell surface ELISA. MMe cells were found to display mild constitutive UPR, as shown by increased levels of GRP78, and presence of the protein at the cell surface, linked to AKT activation. Exposure to EGCG further increased GRP78 in the ER, and induced ATF4, spliced XBP1, CHOP, and EDEM expressions, combined with a reduction of cell surface GRP78 and a rise in caspase 3 and 8 activities. We propose that GRP78 accumulation in the ER, caused by EGCG, converts constitutive UPR of MMe cells into proapoptotic ER stress. This argues for a possible therapeutic use of EGCG in the treatment of MMe as a co‐drug able to abolish chemoresistance to conventional drugs at tolerable doses. Abstract : Epigallocatechin‐3‐gallate (EGCG) causes GRP78 accumulation in the ER of mesothelioma cells. By this way, EGCG converts constitutive mesothelioma UPR into proapoptotic ER stress.